SUATU KAJIAN TEOLOGIS MIKHA 6:8 TERHADAP PROGRAM KARTU INDONESIA PINTAR (KIP) SEBAGAI UPAYA PEMERINTAH MENGURANGI KEMISKINAN DAN PEMERATAAN PENDIDIKAN - Gidion Wayes (Jurnal Penggerak, 2024)
Good education gives people knowledge and skills in order to be more productive. In this perspective, the country has ask to provide educational services for each its citizens, at least for basic education level. Economy problem is a major factor cause low participation education and height dropout rates are on poor community groups. They don't have funds enough to send children to school, because education does need relative costs big. To fulfill commitments globally, the government Indonesia continues to improve equal distribution of education, especially for groups the poor who for this can't school or drop out for various reasons.